Typology of Pea Producers (Pisum sativum L.) in the Municipalities of Córdoba and Puerres, Nariño, Colombia - Zuluaga-Mogollón, María Victoria; Romero-Barrea, Yajaira; Cadena-Pastrana, Alvaro Mauricio (Universidad Pedagógica y Tecnológica de Colombia, 2023)
Fresh pea is the second most important legume in Colombia after beans. In the last 15 years, the cultivated area in the country has increased, and the department of Nariño contributes 58% of the national production. The production area is concentrated in the subregion of former province of Obando, in the south of the department, and is cultivated mainly by smallholders. This crop is one of the most representative agricultural production systems in the region, a key element of food and nutrition security and one of the main sources of income for rural families. This study identified the typologies of producers in the municipalities of Puerres and Córdoba (Nariño) based on a sample of 117 peas to which a structured survey was applied; the data were analyzed using a hierarchical method and four groups of adopters were established. The main differentiating variables were socio-demographic variables, crop experience, technology adoption and its relationship with quality of life and migration processes. This type of analysis contributes to several purposes, from understanding to a certain extent the complexity of rural societies, as well as defining public policies and identifying key aspects for technology adoption.